Roof region dependent wind potential assessment with different RANS turbulence models. Issue 142 (July 2015) - Toja-Silva, Francisco; Peralta, Carlos; Lopez-Garcia, Oscar; Navarro, Jorge; Cruz, Ignacio
Abstract: The analysis of the wind flow around buildings has a great interest from the point of view of the wind energy assessment, pollutant dispersion control, natural ventilation and pedestrians wind comfort and safety. Since LES turbulence models are computationally time consuming when applied to real geometries, RANS models are still widely used. However, RANS models are very sensitive to the chosen turbulence parametrisation and the results can vary according to the application. In this investigation, the simulation of the wind flow around an isolated building is performed using various types of RANS turbulence models in the open source code OpenFOAM, and the results are compared with benchmark experimental data. In order to confirm the numerical accuracy of the simulations, a grid dependency analysis is performed and the convergence index and rate are calculated. Hit rates are calculated for all the cases and the models that successfully pass a validation criterion are analysed at different regions of the building roof, and the most accurate RANS models for the modelling of the flow at each region are identified. The characteristics of the wind flow at each region are also analysed from the point of view of the wind energy generation, and the most adequate wind turbine model for the wind energy exploitation at each region of the building roof is chosen. Abstract : Graphical abstract: